Przyczynek do badań nad twórczą postawą studentów podczas rozwiązywania zadań matematycznych - Major, Joanna; Powązka, Zbigniew (Annales Universitatis Paedagogicae Cracoviensis | Studia ad Didacticam Mathematicae Pertinentia, 2017)
In this paper, we understand the term ’’creative attitude’’ to denote an action of the learner which consists in undertaking creative activity. This activity can take different forms, such as: discovery, invention, a creative act, etc. We understand ’’discovery’’ to denote a fact which already exists but was unknown to the discoverer. While teaching mathematics, we deal with such an understanding of ’’discovery’’ e.g. when we use the problem method. Thence, subjectively new theorems can emerge during the solving of a mathematical problem by a student. Analyzing the collected research material, we try to determine the ability of students to find various regularities, which arise while solving mathematical problems, and to formulate these regularities in the form of theorems. We also pay attention to errors made by the respondents. The results of these observations may be helpful in assessing various aspects of mathematical activity of the examined individuals.